The road half traveled: agricultural market reform in Sub-Saharan Africa - Kherallah, Mylene; Delgado, Christopher L.; Gabre-Madhin, Eleni Zaude; Minot, Nicholas; Johnson, Michael E. (International Food Policy Research Institute, 2000)
This brief reviews the extensive evidence on agricultural market reforms in Sub-Saharan Africa and summarizes the impact reforms have had on market performance, agricultural production, use of modern inputs, and poverty. It offers eight recommendations for completing the reform process and developing a new agenda for agricultural markets in Sub-Saharan Africa."